Practice Guidelines for Canadian Neurophysiology Laboratories During the COVID-19 Pandemic. (19th January 2021) - Appendino, Juan Pablo; Baker, Steven K.; Chapman, Kristine M.; Dykstra, Tamara; Hussein, Tabrez; Jones, Michelle-Lee; Mezei, Michelle M.; Mirsattari, Seyed M.; Ng, Marcus; Nikkel, Joanne; Obradovic, Vaso; Phan, Cecile; et al.
Abstract: The COVID-19 pandemic has had a major impact on clinical practice. Safe standards of practice are essential to protect health care workers while still allowing them to provide good care. The Canadian Society of Clinical Neurophysiologists, the Canadian Association of Electroneurophysiology Technologists, the Association of Electromyography Technologists of Canada, the Board of Registration of Electromyography Technologists of Canada, and the Canadian Board of Registration of Electroencephalograph Technologists have combined to review current published literature about safe practices for neurophysiology laboratories. Herein, we present the results of our review and provide our expert opinion regarding the safe practice of neurophysiology during the COVID-19 pandemic in Canada.